Foreign Policy Concepts of the New Right in Germany: From Hegemonic Ambitions to Isolation - R. R. Stoianov (Международная аналитика)
In recent years, researchers of far-right radicalism have shown interest in the contribution of radical conservatives to the modern theory of international relations. This study focuses on the ideas of the German intellectual movement of the New Right in the FRG in relation to the challenges of world politics. The aim of the study is to analyze the evolution of the political language of the movement’s representatives according to two stages: the Cold War phase of the second half of the 20th century; and the modern stage of development from 2013 to the present. The methodological basis of the paper is the analysis of political texts within the framework of the Cambridge School of the History of Ideas. This method allows us to identify the political problems and opponents of the New Right, to reproduce the political contexts in which the theorists acted, and to identify the cultural resources of the ideologues’ political language. The findings of the study illustrate that the main challenge of the New Right throughout its existence is to ensure national security and increase the political power of the Federal Republic of Germany. The fulfillment of this goal required the development of a foreign policy concept that would ensure the dominance of the FRG in Continental Europe. Despite the fact that the intellectual sources of the ideology of the New Right were not directly related to the theory of international relations, the theses of the theorists are closest to the school of political realism. At the same time, the pro-European ideological positions of the New Right appear to be constrained and, as a consequence, irrelevant among right-wing populists of Europe and the United States. This conclusion allows us to reject the assertion that the goal of the New Right is to revolutionize the existing system of international relations.